2021
DOI: 10.1080/17461391.2021.1982018
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic response and pulse wave analysis after upper‐ and lower‐body resistance exercise with and without blood flow restriction

Abstract: Resistance exercise (RE) has been shown to elevate hemodynamics and pulse wave reflection. However, the effects of acute RE with blood flow restriction (BFR) on hemodynamics and pulse wave reflection are unclear. The purpose of this study was to evaluate the differences between upper-and lower-body RE with and without BFR on hemodynamics and pulse wave reflection. Twenty-three young resistance-trained individuals volunteered for the study. Hemodynamics and pulse wave reflection were assessed at rest, 10, 25, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Studies analyzing six parameters of vascular stiffness were identified: the augmentation index (AI), corrected AI (AI75), Systemic Vascular Resistance (SVR), Pulse Wave Analysis (PWV), Large-Artery Elasticity Index (LAEI), and Small-Artery Elasticity Index (SAEI). In the case of AI, AI75, SVR, LAEI, and SAEI data were not sufficient to perform calculations: AI: Four studies were identified [ 43 , 44 , 45 , 46 ], but only Amorim et al showed a more decisive influence of BFR over non-BFR exercise [ 43 ]. AI75: None of the three identified studies reported any significance in the change in AI75 between BFR and non-BFR exercise [ 28 , 43 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies analyzing six parameters of vascular stiffness were identified: the augmentation index (AI), corrected AI (AI75), Systemic Vascular Resistance (SVR), Pulse Wave Analysis (PWV), Large-Artery Elasticity Index (LAEI), and Small-Artery Elasticity Index (SAEI). In the case of AI, AI75, SVR, LAEI, and SAEI data were not sufficient to perform calculations: AI: Four studies were identified [ 43 , 44 , 45 , 46 ], but only Amorim et al showed a more decisive influence of BFR over non-BFR exercise [ 43 ]. AI75: None of the three identified studies reported any significance in the change in AI75 between BFR and non-BFR exercise [ 28 , 43 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the case of AI, AI75, SVR, LAEI, and SAEI data were not sufficient to perform calculations: AI: Four studies were identified [ 43 , 44 , 45 , 46 ], but only Amorim et al showed a more decisive influence of BFR over non-BFR exercise [ 43 ]. AI75: None of the three identified studies reported any significance in the change in AI75 between BFR and non-BFR exercise [ 28 , 43 , 45 ]. SVR: According to Karabulut et al, BFR exercise is more effective for decreasing SVR than low-intensity non-BFR exercise but less effective compared to high-intensity non-BFR training [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations